Fiscal Federalism and Its Role in Optimization of the Financial Sistem Country - Abuselidze, George (International Journal of Management and Sustainability, 2013)
To optimize the financial system is exceptionally important to achieve an effective balance between revenues and expenditures of all-the central, regional and local budgets. Socio-economic development of regions cannot be accomplish without financial relations. "Fiscal federalism" multilateral and, respectively complex mechanism, which describes the financial device of rights and obligations between the "center" and "region", the rules of their relationship at all stages of the budget process, regulatory and legislative methods of budgetary resources redistribution. In the process of formation, distribution and exercising of public finances socio- economic relations between the State, legal entities and individuals are build and at the same time subjective interests are realized.